Local residents' attitudes about wind farms and associated noise annoyance in South Korea. (April 2022) - Ki, Jaehong; Yun, Sun-Jin; Kim, Woo-Chang; Oh, Subin; Ha, Jihun; Hwangbo, Eunyoung; Lee, Hyoeun; Shin, Sumin; Yoon, Seulki; Youn, Hyewon
Abstract: Although the deployment of wind energy has gradually increased in South Korea, local opposition to the development of wind projects has frequently been reported; this could retard the deployment of wind power in South Korea. Noise from the operation of wind turbines is claimed to be the major reason for opposition. This study explored factors related to local residents' attitudes toward adjacent wind farms and the noise annoyance associated with them. Multivariate linear regression models were adopted to analyze a survey conducted in three counties in South Korea. In the analysis of attitudes, the perceived fairness of the development process was the most influential independent variable, followed by visual evaluation of wind farms and thoughts on whether more wind energy should be installed within the country. In the analysis of noise annoyance, current attitude toward existing wind farms was the most influential factor, followed by factors related to the visibility of wind farms and visual evaluation of them. These findings suggest that planning processes that engage local residents from the start of project development and empower them to influence wind farm layout designs are effective in securing community acceptance and even in alleviating the perceived annoyance of wind turbine noise. Highlights: This study investigated attitudes to and noise annoyance of wind farms in S. Korea. Perceptions of the fairness mainly determines attitudes towards local wind farms. Noise annoyance was related to the visibility of wind facilities, not distance. Residents' engagement in planning processes is a key for wind farm acceptance.